2021
DOI: 10.3390/app11178273
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Pentoxifylline: Profiling Data Based on RAW 264.7 Cellular Signaling

Abstract: Pentoxifylline (PTX) is a methylxanthine derivative that has been developed as an immunomodulatory agent and an improvement of microcirculation. Osteoradionecrosis (ORN) is a serious complication of radiation therapy due to hypovascularity. Coronavirus disease 2019 (COVID-19) has spread globally. Symptoms for this disease include self-limiting respiratory tract illness to severe pneumonia and acute respiratory distress. In this study, the effects of PTX on RAW 264.7 cells were investigated to reveal the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…Arsenyan et al [ 28 ] showed that PTX did not significantly suppress the MMP-mediated endothelial invasion in their study on the human umbilical vein endothelial cell tube formation model. This contrasts with the findings of Seo et al [ 43 ], which show that MMP-2 was upregulated in the 24 h post administration of pentoxifylline yet down-regulated after 48 h in a mouse-derived macrophage cell line. These findings suggest that metalloproteinase levels may be transiently affected by pentoxifylline.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Arsenyan et al [ 28 ] showed that PTX did not significantly suppress the MMP-mediated endothelial invasion in their study on the human umbilical vein endothelial cell tube formation model. This contrasts with the findings of Seo et al [ 43 ], which show that MMP-2 was upregulated in the 24 h post administration of pentoxifylline yet down-regulated after 48 h in a mouse-derived macrophage cell line. These findings suggest that metalloproteinase levels may be transiently affected by pentoxifylline.…”
Section: Discussioncontrasting
confidence: 99%
“…All of the included studies were laboratory studies that examined the ability of pentoxifylline to generate an effect on angiogenesis in various models. Fifteen studies were in vivo only [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], three studies were in vitro only [ 41 , 42 , 43 ], and four studies had both in vivo and in vitro models [ 44 , 45 , 46 , 47 ]. The in vitro studies used human cells [ 42 , 44 , 45 , 46 , 47 ] and mouse cell lines [ 41 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations